1998
DOI: 10.1159/000069462
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Small Intestinal Lesions in Anaphylaxis of Rats

Abstract: Hemorrhage and congestion were not uniformly distributed along the small intestine during systemic anaphylaxis in rats. Duodenum had little hemorrhage and congestion and the terminal ileum had even less. Maximum involvement occurred in jejunum of 13% of rats, in ileum of 47%, and in both jejunum and ileum of 40%. Sequential scoring along the entire length of small intestine revealed different patterns of distribution with more than one peak of intensity in some of the rats. Within a lesioned area, banding was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
3
2
0
Order By: Relevance
“…The small intestine of congenic normal mice exhibited findings similar to those described for intestinal anaphylaxis in experimental animal models ( Fig. 4B; D 'Inca et al 1990;Levine et al 1998;Li et al 1999), but these intestinal alterations were nearly absent in mastcell-deficient mice.…”
Section: Histopathologic Findingssupporting
confidence: 79%
See 1 more Smart Citation
“…The small intestine of congenic normal mice exhibited findings similar to those described for intestinal anaphylaxis in experimental animal models ( Fig. 4B; D 'Inca et al 1990;Levine et al 1998;Li et al 1999), but these intestinal alterations were nearly absent in mastcell-deficient mice.…”
Section: Histopathologic Findingssupporting
confidence: 79%
“…All of the congenic normal mice treated with praziquantel 8 weeks after S. japonicum infection exhibited systemic signs typical in rodent models of systemic anaphylaxis (D'Inca et al 1990;Levine and Saltzman 1998;Li et al 1999). The animals exhibited labored respiration, cyanosis and no activity immediately after praziquantel administration, findings which were associated with a gradual decrease in rectal temperature (Fig.…”
Section: Systemic Signsmentioning
confidence: 90%
“…It seems that these mucosal lesions of the small intestine relate to the cause of gastrointestinal leakage of LYZ as an antigen, Furthermore, in this experiment, we also observed slight damage to the villi of the small intestine of the sensitized mice that were not exercised. The histologic appearance was essentially the same as that described in intestinal anaphylaxis in rats (Levine and Saltzman 1998) and mice (Li et al 1999). Li et al (1999) reported intestinal permeability after intragastric allergen challenge in sensitized mice.…”
Section: Discussionsupporting
confidence: 62%
“…In our experiments hemorrhage occurred in all segments of the small intestine being more intense in jejunum and ileum than in the duodenum corroborating previous finding by Levine and Saltzman [13]. However in their study the lesions were more intense in jejunum than in duodenum and ileum.…”
Section: Discussionsupporting
confidence: 92%